The Influence of Islamic Business Ethics, and Service Quality on Customer Satisfaction through Corporate Image - Ramlah Ramlah; Amiruddin K; Sudirman Sudirman (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2026)
The purpose of this study is to examine how customer satisfaction is affected directly by Islamic business ethics and service quality, as well as indirectly by both factors using corporate image as an intervening variable at the Al-Badar Syariah Hotel Makassar. The study employs a descriptive quantitative methodology, and the research sample consists of 200 respondents who completed a questionnaire that collected primary data. The Structural Equation Model (SEM), which combines outer and inner model analysis with hypothesis testing to investigate the relationship between variables simultaneously and thoroughly, is the data analysis method employed. The findings demonstrate that customer Satisfaction and Corporate image are positively and significantly impacted by Islamic business ethics. It has also been demonstrated that customer satisfaction and corporate image are significantly impacted by service quality. Additionally, consumer satisfaction is significantly impacted by the company's image. Another significant study supports the strategic function of Corporate image as an intervening variable by demonstrating that Islamic business ethics and service quality indirectly affect customer satisfaction through corporate image. The management of Hotel Al-Badar Makassar might utilize the study's findings as a guide when developing sharia-based service plans to enhance patron happiness and experience.